Perancangan Sistem Informasi Stok Barang Terpadu pada Toko Handphone di Pasar Singosaren Surakarta - Sukadi, Sukadi; Rendrarini, Diana (LPPM Universitas Merdeka Madiun, 2020)
Abstractâ€” Singosaren Market or also known by the people of Surakarta City and its surroundings with Matahari Singosaren is one of the centers of Mobile Phones or Smartphones in Surakarta City. Singosaren Market was first built in 1988, at first the first floor was clothing stalls but starting in 2000 the first floor was changed to a mobile shops. Mobile phone sellers in their daily lives if there are buyers who want to buy goods and the seller of the stock is empty, then the sellers will ask other sellers whether the stock is still there or empty. To speed up or help sellers get information on which stores are not empty, in this study a Integrated Inventory Information System Design for Mobile Stores in Singosaren Market Surakarta was designed, which is expected to be applied in the future at mobile shops in Singosaren Market Surakarta.Â Keywordsâ€”: Goods Stock; Mobile; Singosaren Market.